Synergistic effect of albuminuria on atherosclerosis in patients with primary aldosteronism - Ting-Wei Kao; Che-Wei Liao; Cheng-Hsuan Tsai; Yi-Yao Chang; Chien-Ting Pan; Chin-Chen Chang; Bo-Ching Lee; Wei-Chieh Huang; Kuo-How Huang; Ching-Chu Lu; Tai-Shuan Lai; Chieh-Kai Chan; et al. (SAGE Publishing, 2023)
Background: Primary aldosteronism (PA) has been associated with atherosclerosis beyond the extent of essential hypertension, but the impact of albuminuria remains unknown. Objective: To investigate the effect of concomitant albuminuria on arterial stiffness in PA. Design: Prospective cohort study. Methods: A prospective cohort study was conducted to evaluate the association of albuminuria (>30 mg/g in morning spot urine) with arterial stiffness, as measured non-invasively by pulse wave velocity (PWV) in patients with PA. Propensity score matching (PSM) with age, sex, diabetes, systolic and diastolic blood pressure, creatinine, potassium, number of antihypertensive medications, and hypertension history was used to balance baseline characteristics. The effects of albuminuria on PWV before and 1 year after treatment were analyzed. Results: A total of 840 patients with PA were enrolled, of whom 243 had concomitant albuminuria. After PSM, there were no significant differences in baseline demographic parameters except alpha-blocker and spironolactone use. PWV was greater in the presence of albuminuria ( p  = 0.012) and positively correlated with urine albumin-creatinine ratio. Multivariable regression analysis identified albuminuria, age, body weight, systolic blood pressure, and calcium channel blocker use as independent predictors of PWV. As for treatment response, only PA patients with albuminuria showed significant improvements in PWV after PSM ( p  = 0.001). The magnitude of improvement in PWV increased with urine albumin-creatinine ratio and reached plateau when it exceeded 100 mg/g according to restricted cubic spline analysis. Conclusion: Concomitant albuminuria in PA was associated with greater arterial stiffness and more substantial improvement after targeted treatment. Both the baseline and the improved extent of PWV increased in correlation with rising urine albumin-creatinine ratio levels, reaching a plateau when the urine albumin-creatinine ratio surpassed 100 mg/g.